2018
DOI: 10.1021/acs.jpcb.7b11668
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Protein Dynamics from Experimental Structure Ensembles, Molecular Dynamics Ensembles, and Coarse-Grained Elastic Network Models

Abstract: Predicting protein motions is important for bridging the gap between protein structure and function. With growing numbers of structures of the same or closely related proteins becoming available, it is now possible to understand more about the intrinsic dynamics of a protein with principal component analysis (PCA) of the motions apparent within ensembles of experimental structures. In this paper, we compare the motions extracted from experimental ensembles of 50 different proteins with the modes of motion pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In spite of this simplicity, it soon became evident that ENMs can not only predict residue fluctuations, but are also capable of guessing with striking precision the directions of large-scale transitions between e.g., X-ray open and closed pairs (Tama and Sanejouand, 2001). Later work has shown that ENMs reproduce as well the flexibility from experimental X-ray and NMR ensembles, or long MD simulations (Rueda et al, 2007; Orellana et al, 2010; Mahajan and Sanejouand, 2015; Sankar et al, 2018) and importantly, track the pathways for conformational change (Orellana et al, 2016; see NM projections, Figure 1C, left). Therefore, ENMs have been at the core of CG-strategies to find transition paths; however, being limited to an equilibrium basin, pathway generation requires iterative deformation along selected NMs, or implementation into some simulation scheme.…”
Section: Path-finding Methods: Throwing Ropes Over Mountainsmentioning
confidence: 83%
“…In spite of this simplicity, it soon became evident that ENMs can not only predict residue fluctuations, but are also capable of guessing with striking precision the directions of large-scale transitions between e.g., X-ray open and closed pairs (Tama and Sanejouand, 2001). Later work has shown that ENMs reproduce as well the flexibility from experimental X-ray and NMR ensembles, or long MD simulations (Rueda et al, 2007; Orellana et al, 2010; Mahajan and Sanejouand, 2015; Sankar et al, 2018) and importantly, track the pathways for conformational change (Orellana et al, 2016; see NM projections, Figure 1C, left). Therefore, ENMs have been at the core of CG-strategies to find transition paths; however, being limited to an equilibrium basin, pathway generation requires iterative deformation along selected NMs, or implementation into some simulation scheme.…”
Section: Path-finding Methods: Throwing Ropes Over Mountainsmentioning
confidence: 83%
“…For instance, parameter sets for network models have been introduced that delineate different inter-residue coupling forces to reproduce experimental Debye-Waller factors [46]. On the basis of statistical distributions of residue contacts observed in training sets of experimental structures, it is possible to formulate hybrid network/native-contact models that capture pairwise energies [47], vibrational entropies [42,43], relative entropies [48,49], and maintained contacts [50]. In the case of intrinsically disordered proteins, in which native states are largely unknown, large datasets of radius of gyrations were used to parameterize effective CG potentials.…”
Section: Coarse-grained Modeling Of Large Biomoleculesmentioning
confidence: 99%
“…30,31 Previous studies showed that these simple models can efficiently capture the functional dynamics of proteins 32,33 and that the global dynamics derived with Elastic Network Model (ENM) shows strong overlap with the motions from atomistic molecular dynamic simulations. 34,35 Some of these dynamical features include mean-square fluctuations of residues and the resilience of residues to external perturbations given by dynamic flexibility index (DFI). 36 For prediction of allosteric residues, we specifically consider the shortest dynamically correlated path between a given residue and the active site residues and the effect of perturbing the active site residues on a given residue.…”
Section: Introductionmentioning
confidence: 99%
“…In our models, we include features that describe the dynamic behavior of residues in a protein molecule by using elastic network models . Previous studies showed that these simple models can efficiently capture the functional dynamics of proteins and that the global dynamics derived with Elastic Network Model (ENM) shows strong overlap with the motions from atomistic molecular dynamic simulations . Some of these dynamical features include mean‐square fluctuations of residues and the resilience of residues to external perturbations given by dynamic flexibility index (DFI) .…”
Section: Introductionmentioning
confidence: 99%